ANALISIS DATA UJIAN NASIONAL SEBAGAI INDIKATOR KEBERHASILAN SISTEM PENDIDIKAN - Tiara lisa br Tarigan; Nur Intan; Syahira Auty (CV. Adiba Aisha Amira, 2023)
This research aims to conduct an in-depth analysis of National Examination data as an indicator of the success of the education system at the national level. Quantitative analysis methods are used to identify significant trends and patterns in test results, provide insight into student achievement, and evaluate the effectiveness of the education system. The data collected involved a large number of examinees from various levels of education. The analysis was carried out using statistical techniques to measure the distribution of grades, graduation rates, and comparison of achievements between subjects. In addition, this research also explores external factors that can influence exam results, such as student participation levels, resource availability, and learning environment characteristics. It is hoped that the results of this research can make a significant contribution to understanding the effectiveness of the national education system. The policy implications that may result from these findings can help policy makers in designing strategies to improve the overall quality of education, identify areas that require special attention, and design appropriate interventions to increase student success in the National Examination.